Analysis and Design of Doctors Credit Points for Functional Position in Paru Hospital Surabaya - Putra, Andreas Alfred Savero; Wibowo, Januar; Alif Fianto, Achmad Yanu (Jurnal Sistem Informasi Universitas Dinamika (JSIKA), 2018)
In Paru Hospital of Surabaya, every doctor in charge had points that based on any activities carried out by the doctor in the scope of Paru Hospital of Surabaya. Doctors in Paru Hospital of Surabaya ahve a list of activities summarized according to Joint Decree of the Minister of Health and Head of the State Personnel Agency Number 1738 / MENKES / SKB / XII / 2003 Number 52 of 2003 concerning Implementation Guidelines for Doctor's Functional Position and Credit Score. In the permenkes mentioned thatÂ doctorâ€™s activities and kredit figured are outlined which can be used as preference for the functional promotion of doctors in Paru Hospital Surabaya. Until now there are still No. facilitesfor doctors in Paru Hospital of Surabaya to record their kredit nubers for doctor promotion in Paru Hospital of Surabaya. Solution made by the author of this journal is Paru Hospital of Surabaya need a web-based application that make doctor easily to record their activities during certain period of time